Residents' attitude toward tourism development in Isfahan, Iran / Pooyan Ghomsheh - Ghomsheh, Pooyan (2015)
In numerous countries of the world, tourism is regarded as an effective vehicle to encourage rural economic development. However, tourism can also obliterate the wealth on which its growth depends. In view of the above, tourism planning has incorporated an essential reflection of local residents' attitude toward tourism throughout the planning process. Therefore, the purpose of this study is to understand residents' attitudes toward tourism development in Isfahan, Iran.This study was designed based on the application of social exchange theory (SET). SET has a social psychological and sociological perspective that explains social change and stability as a process of negotiated exchanges between people in society. SET theorists argue that all human relationships are formed by using a subjective cost-benefit analysis and the comparison of alternatives. Social exchange theory (SET) has been adapted widely by tourism researchers since the 1990s. The present study used a survey design to achieve its objectives in which cluster sampling was employed. A total of 289 respondents participated from among residents in Isfahan, Iran and for analyzing the data using SPSS version 20. The most common residents' support for tourism development is "I favor building new tourism facilities which will attract more tourists". The result of current study showed that the average of support for tourism development among resident Isfahan was higher than moderate level. The most common residents' attitude toward tourism is related to "Should encourage tourism in Isfahan". The most common negative impact of tourism belonged to "The prices of goods and services will increase because of tourism". The important negative impact of tourism is related to the economic and cultural aspect. The most common positive impact of tourism is related to "Tourism has provided an incentive for the restoration of historical buildings". The result also showed that the level of perceived positive impact of tourism was significantly higher than perceived negative impact. There was a positive relationship between attitude toward tourism and tourism. The findings revealed that the tourism impacts mediated the effect of attitude on tourism development. Age, level of contact with tourists and living duration in Isfahan showed a positive relationship with tourism development.